Non–Vitamin K Antagonist Oral Anticoagulants in Patients With Atrial Fibrillation and Prior Gastrointestinal Bleeding. Issue 2 (February 2021) - Kwon, Soonil; Lee, So-Ryoung; Choi, Eue-Keun; Lee, Euijae; Jung, Jin-Hyung; Han, Kyung-Do; Cha, Myung-Jin; Oh, Seil; Lip, Gregory Y.H.
Abstract : Background and Purpose: Limited data support the benefits of non–vitamin K oral anticoagulants (NOACs) among atrial fibrillation patients with prior gastrointestinal bleeding (GIB). We aimed to evaluate the effectiveness and safety of NOACs compared with those of warfarin among atrial fibrillation patients with prior GIB. Methods: Oral anticoagulant–naive individuals with atrial fibrillation and prior GIB between January 2010 and April 2018 were identified from the Korean claims database. NOAC users were compared with warfarin users by balancing covariates using the inverse probability of treatment weighting method. The primary outcomes were ischemic stroke, major bleeding, and the composite outcome (combined ischemic stroke and major bleeding). Fatal events from each outcome were evaluated as secondary outcomes. Results: A total of 42 048 patients were included (24 781 in the NOAC group and 17 267 in the warfarin group). The mean time from prior GIB to the initiation of oral anticoagulant was 3.1±2.6 years. After inverse probability of treatment weighting, baseline characteristics were balanced between the two groups (mean age, 72 years; men, 56.8%; and mean CHA2 DS2 -VASc score, 3.7). Lower risks of ischemic stroke, major bleeding, and the composite outcome were associated with NOAC use than with warfarin use (weighted hazard ratio, 0.608 [95% CI, 0.543–0.680]; hazard ratio, 0.731 [95% CI, 0.642–0.832]; and hazard ratio, 0.661 [95% CI, 0.606–0.721], respectively). For all secondary outcomes, NOACs showed greater risk reductions compared with warfarin. Conclusions: NOACs were associated with lower risks of ischemic stroke and major bleeding than warfarin among atrial fibrillation patients with prior GIB. Abstract : Supplemental Digital Content is available in the text.